EXPERIMENTAL ANALYSIS OF MODERN STATE OF REPRODUCTION FOR CHERRY SALMON ONCORHYNCHUS MASOU AT THE FISH FARMS OF SAKHALIN REGION - M. S. Myakishev; M. A. Ivanova; V. A. Kiselev; O. V. Zelennikov (Известия ТИНРО)
Growing of cherry salmon juveniles under two different temperature regimes at the salmon farms Anivsky and Okhotsky in the fish-rearing cycle of 2016–2017 is analyzed. Data on cherry salmon growing for other fish farms of Sakhalin region collected in 1995–2017 are considered, as well. The periods of fish feeding and dynamics of their growth varied significantly in dependence on temperature conditions. The feeding started in April-May at the cold-water fish farms (Anivsky, Lesnoy, Sokolovsky, Urozhainiy) where the water temperature lowered in winter to 0.2–0.3 о С, but in February at Reidovo fish farm where the water temperature were not lower than 2 о С and in January at the most warm-water Okhotsky fish farm with the temperature never lower than 6.5 о С. In accordance with growing conditions, the growth rate of juveniles was high in winter month at the warm-water fish farms, where the ground water was used for rearing, but increased since May-June at the cold-water fish farms using natural heating of the river water. However, several cases were noted when the fish that accumulated less than 500–700 degree-days released from cold-water fish farms in June-July were larger than those from warm-water fish farms. Thus, cherry salmon is the only species among pacific salmons whose juveniles can be successfully grown at any temperature regime and consequently at any fish farm. This ability is reasoned by earlier spawning (along with pink salmon) and long period of development in rivers. At cold-water fish farms, the best results for cherry salmon growing could be achieved with the eggs planting in late August-September, whereas the time of eggs planting is not significant for warm-water fish farms.